The impact of cooking methods on the nutritional quality and safety of chicken breaded nuggets. Issue 6 (23rd May 2016) - Gonçalves Albuquerque, Tânia; Oliveira, M. Beatriz P. P.; Sanches-Silva, Ana; Cristina Bento, Ana; Costa, Helena S.
Abstract : The impact of cooking methods (industrial pre-frying, deep-fat frying and baking) on the nutritional quality and safety of chicken breaded nugget samples from supermarket and commercial brands was evaluated. Abstract : The impact of cooking methods (industrial pre-frying, deep-fat frying and baking) on the nutritional quality and safety of chicken breaded nugget samples from supermarket and commercial brands was evaluated. The changes in the quality characteristics (nutritional composition, fatty acids profile, cholesterol and salt) of the fried food and frying oil, after ten consecutive frying operations, were evaluated. The total fat content of nuggets varied between 10.9 and 22.7 g per 100 g of edible portion and the salt content ranged from 0.873 to 1.63 g per 100 g. Taking into account one portion of nuggets, the daily intake of salt can reach 49%, which can have a significant impact on the health of those who regularly consume this type of food, especially considering the prevalence of hypertension around the world. The analysed chicken breaded nuggets are rich in unsaturated fatty acids, which have been related with potential health benefits, namely regarding cardiovascular diseases. The cholesterol content of baked samples was two times higher when compared with the fried ones. The trans fatty acids and polar compounds contents of the frying oil used for frying significantly increased, but the values were still away from the maximum recommended by legal entities for its rejection. From a nutritional point of view, it is possible to conclude that the applied cooking methods can significantly influence the nutritional quality and safety of the analysed chicken breaded nuggets. This study will contribute to important knowledge on how the applied cooking methods can change the nutritional quality and safety of foods, namely of chicken nuggets, and can be very useful for dietary recommendations and nutritional assessment.